SISTEM INFORMASI BUKU PENGHUBUNG PENILAIAN KARAKTER SISWA SDIT LUQMAN AL-HAKIM MERAUKE - Nugraha, Syaiful; Sumaryanti, Lilik; Iqbal, Muhammad (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Mataram, 2024)
The connecting book is an administrative form prepared by Elementary School (SD) teachers to serve as an indirect communication tool for conveying important information about a child's development at school. SDIT Al-Hakim Merauke, one of the schools that implements the communication book system, currently still uses a manual method to fill out the book. This process is carried out by homeroom teachers with the aim of providing information and assessments of students' behavior at school to their parents. However, manual entry makes the communication book vulnerable to damage and the possibility of loss. In addition, the number of communication books that each teacher must manage also makes the recording process less efficient. Therefore, the background of this research is to develop a web-based informaton system aimed at assisting homeroom teachers and parents in the communication book recording process, as well as presenting students' progress at school more efficiently. The creation and development of this system use the Waterfall approach, utilizing PHP programming language and MySQL as the database management. Thus, the result of this research is an application that can provide information effectively and efficiently. The User Acceptance Test results indicate that 87.63% of users indicate that this communication book application can facilitate homeroom teachers and parents in the communication book recording process and provide information about students' development and activities at school.